Pengembangan Usaha Agroindustri Noni (mengkudu) dengan Pendekatan Decission Support System - Andika Putra Setiawan; Abdoel Djamali; Danang Kumara Hadi; Risa Martha; Satriya Bayu Aji (Kadiri University, 2021)
Noni or pace (Morinda citrifolia) is a medicinal plant with much interest from entrepreneurs in the traditional medicine industry and researchers in various countries. This study aimed to design the development of an agro-industry business (UD. ZAM) to increase competitiveness. The design of this research was descriptive using the expert system method. The analysis technique employed the MSME DSS software version 2.0 with a legal, marketing, management, human resources, environmental, and financial analysis model to design a Decision Support System. The results obtained were that UD. ZAM already had complete business legalization, such as Company Registration Certificate (TDP) 13.07.5.47.25386, Trading Business License (SIUP) 503/0087/411/2015, Taxpayer Identification Number (NPWP) 72.691.633.1-626.000, and Permit Industrial Business (IUI) 503/3212/411/2015, and P-IRT NO2133509103570-21. Therefore, with the license certificate, UD. ZAM was legal. In the marketing of noni products so far, it is export-oriented, which has advantages so that it can be developed. In terms of production performance, it shows the required production process and aspects of human resources provided by UD. ZAM standard regional minimum wage (UMR) and employment in rural areas, in a high feasibility environment, because it was easy to obtain materials and in financial aspects such as the assumption of an interest rate of 15%, break event point (BEP) quantity 25,833.87 and ( BEP) sales 261.397.03.77, benefit coast ratio (BCR) 2.35, payback period 1.23, net present value (NPV) 18.066.137.185.78, probability index (PI) 11, 28, and internal rate of return (IRR) 56.44. Keywords: Noni Agroindustry; Decision Support System (DSS).Mengkudu (Morinda citrifolia) adalah tanaman obat yang banyak peminatnya dari kalangan pengusaha industri obat tradisional dan peneliti diberbagai negara. Penelitian ini bertujuan untuk merancang pengembangan usaha agroindustri UD. ZAM untuk meningkatkan daya saing. Rancangan penelitian ini adalah deskriptif menggunakan metode expert system. Teknik analisis menggunakan software DSS UMKM version 2.0 dengan model analisis aspek hukum, aspek pemasaran, aspek produksi, aspek manajemen dan sumber daya manusia, aspek lingkungan, dan aspek keuangan. Hasil penelitian yang diperoleh adalah UD. ZAM telah memiliki kelengkapan legalisasi usaha Tanda Daftar Perusahaan (TDP) 13.07.5.47.25386, Surat Izin Usaha Perdagangan (SIUP) 503/0087/411/2015, Nomor Pokok Wajib Pajak (NPWP) 72.691.633.1-626.000, Izin Usaha Industri (IUI) 503/3212/411/2015, dan P-IRT NO2133509103570-21. Pemasaran produk noni selama ini berorientasi ekspor yang memiliki kelebihan kepastian pasar sehingga layak untuk dikembangkan, pada aspek kinerja produksi menunjukkan tingkat kelayakan rendah, aspek sumber daya manusia sistem upah yang diberikan oleh UD. ZAM standart Upah Minimum Regional (UMR) dan memberi lapangan pekerjaan pada masyarakat pedesaan, pada aspek kinerja lingkungan tingkat kelayakan tinggi, karena selama ini mudah untuk mendapatkan bahan baku, pada aspek keuangan seperti asumsi tingkat bunga sebesar 15%, break event point (BEP) kuantitas 25.833.87 maupun (BEP) penjualan 261.397.03,77,benefit coast ratio (BCR) 2,35, payback period 1,23, net present value (NPV) 18.066.137.185,78, probability index (PI) 11,28, dan internal rate of return(IRR) 56,44 maka layak dikembangkan lebih lanjut